ECONOMIC ANALYSIS OF COCONUT-BASED MIXED FARMING SYSTEMS - H. P. Maheswarappa; C. V. Sairam; R. Dhanapal; T. Vidhan Singh; M. R. Hegde (International Coconut Community Journal, 2000)
Coconut-Based Mixed Farming System which evolved from the Central Plantation Crops Research Institute is one of the technologies recommended for sustainable coconut production. The economic analysis of this system for the period 1989-90 to 1997-98, realized a net return between Rs. 49,700 to Rs. 126,900. The Cash Flow Analysis preformed using a discount rate of 14% realized the Benefit-Cost Ratio (BCR) of 1.36, the Net Present Worth of the system was Rs.286,500,, the Internal Rate of Return was 27.44%, and, the Pay Back Period was five years.